Ideal Downward Refinement in the EL Description Logic - Lehmann, J; Haase, C (Springer, 2009)
With the proliferation of the Semantic Web, there has been a rapidly rising interest in description logics, which form the logical foundation of the W3C standard ontology language OWL. While the number of OWL knowledge bases grows, there is an increasing demand for tools assisting knowledge engineers in building up and maintaining their structure. For this purpose, concept learning algorithms based on refinement operators have been investigated. In this paper, we provide an ideal refinement operator for the description logic EL and show that it is computationally feasible on large knowledge bases.